"Push‐button" noncontrast MR angiography using balanced T1 relaxation‐enhanced steady‐state (bT1RESS). Issue 3 (16th September 2020) - Edelman, Robert R.; Koktzoglou, Ioannis
Abstract : Purpose: We introduce a MR imaging technique, balanced T1 relaxation‐enhanced steady‐state (bT1RESS), that provides the unique capability to efficiently impart a flexible amount of T1 weighting to a balanced steady‐state free precession acquisition using periodically applied contrast‐modifying RF pulses. Leveraging this capability to suppress the signal intensity of background tissues, we implemented a 3D noncontrast MR angiography technique that continuously acquires thin overlapping 3D volumes and tested it for evaluation of the peripheral arteries. Methods: bT1RESS used a fast interrupted steady‐state readout with a 45° cslab‐selective ontrast‐modifying RF pulse applied at 262 msec intervals. A series of 16.4‐mm thick overlapping 3D volumes was acquired using a radial stack‐of‐stars k‐space trajectory. The combination of slice oversampling, slab overlap, and averaging of edge slices was helpful to reduce venetian blind artifact. Spatial resolution was near isotropic with reconstructed slice thickness = 0.7 mm and in‐plane resolution = 0.5 mm. Results: Pilot studies in the peripheral arteries demonstrated improved vessel sharpness compared with cardiac‐gated quiescent interval slice‐selective noncontrast MR angiography. bT1RESS noncontrast MR angiography reliably identified stenotic and occlusive arterial disease in a small cohort of patients with peripheral artery disease. Conclusions: bT1RESS provides the basis for a simplified, completely "push button" approach for noncontrast MR angiography that obviates the need for contrast agents, electrocardiographic gating, scout imaging, breath holding, or tailoring of imaging parameters for the individual patient. Further work is needed for technical optimization and clinical validation.